Compensation of frequency selectivity and antenna effect for the energy detection Gaussian frequency‐shift keying ultra‐wideband system. Issue 3 (8th March 2016) - Cui, Song; Xiong, Fuqin
Abstract : The energy detection (ED) Gaussian frequency‐shift keying (GFSK) ultra‐wideband (UWB) system, transmits bit 0 and 1 using different‐order derivatives of the Gaussian pulse. The spectra of the two pulses are separated entirely in the frequency domain, so it generates the orthogonality of these two pulses. This orthogonality in the frequency domain makes the GFSK system more robust in multipath channels and in the presence of synchronisation errors, so it shows a better bit error rate performance than the ED pulse‐position modulation UWB system. However, the effect of frequency selectivity and antenna has not been discussed in earlier publications. In this study, the authors will analyse the effect of these two factors and propose a method to compensate the effect.